DIRECT SYNTHESIS OF DIMETHYL ETHER (DME) USING MIXED CATALYST OF METHANOL SYNTHESIS AND METHANOL DEHYDRATION - Andini, Puji
Dimethyl ether (DME) is an alternative fuel for LPG that is environmentally friendly. DME and LPG have similar characteristics, both chemical and physical properties, so they can utilize the existing LPG infrastructure. The production of DME from syngas can be carried out by two different processes, namely a two-step process or indirect synthesis of DME and direct synthesis of DME. The two-step process involves the synthesis of methanol with a Cu-based catalyst and dehydration of methanol with an acid catalyst in different reactors, while the direct synthesis of DME is an integration of methanol synthesis and its dehydration that carried out in a single reactor using a mixture of both catalysts. It is known that the activity of the two catalysts used in the direct synthesis of DME from syngas can be decreased in the presence of water. However, during the direct synthesis of DME, water production is inevitable. A mixed of two different types of catalysts—XAB for methanol synthesis and a 5% P/5% Al2O3 or 5P/Al catalyst for methanol dehydration—was used to synthesize DME. The syngas used in this synthesis has a composition of 65% H2, 28% CO, and 7% N2 with a flow rate of 20 mL/min. The synthesis was carried out in two different sets of operating conditions. Set-1 was completed for 24 hours at 260 oC and 5–20 bar and Set-2 was done for 24 hours at 18 bar and 250–290 oC. Direct synthesis of DME was also carried out with the addition of molsieve 4A at Set-1, and molsieve 3A at Set-2. Molsieve 4A and molsieve 3A are used as an absorbent to absorb H2O from the reaction so that the reaction equilibrium always shifts towards the product. In the direct synthesis of DME without an adsorbent, the optimal catalyst performance (XAB):(5P/Al) at Set-1 occurred at a pressure of 18 bar, with the coversion of CO by 74% and the yield of DME by 8.2%. In Set-2, the optimal catalyst performance occurred at 270 oC, with the conversion of CO by 73.8% and the yield of DME gain by 6.8%. The addition of molsieve 4A as an in-situ H2O adsorbent in the continuous process of direct synthesis DME had no effect on the productivity of DME, given that the placement of the adsorbent was inappropriate, and the pore diameter of the adsorbent was larger than methanol so that it has the potential to absorb the synthesized methanol. The conversion of CO increased with the addition of molsieve 3A under the same operating condition as Set-2 compared to experiment without the adsorbent. At 270 oC (considered the optimal temperature), the conversion of CO rate increased to 85.8%. At 290 oC, the yield of DME increased from 4.5% to 7.2%.